Individualism and the social order : the social element in liberal thought - McCann, Charles R. (Charles Robert), 1956- (Routledge frontiers of political economy ;, 2004)
Liberalism is typically misconceived as a philosophy of individualism, which cannot accept that man exists in society and that man's values are shaped by that society. This book attempts to identify the role of community and society in the political and social thought of leading liberal social philosophers of the 19th and 20th centuries including John Stuart Mill, Herbert Spencer and Friedrich A. von Hayek. While differing as to the nature of man and society, each thinker examined holds the basic premise that man is not an isolated creature whose life is 'nasty, brutish and short' but r.